2022
DOI: 10.12720/jcm.17.1.11-16
|View full text |Cite
|
Sign up to set email alerts
|

Improved One-Dimensional Piecewise Chaotic Maps for Information Security

Abstract: Chaos represents interesting features that are suitable for the cryptography domain. One-dimensional chaotic maps are widely used for security issues due to their simplicity and chaotic behavior versus other multidimensional chaotic maps that can be complex for hardware implementation and hard to analyze. However, classical one-dimensional chaotic maps present a reduced range of chaotic behavior. In this paper, we propose two new piecewise compound one-dimensional chaotic maps; an Altered Sine-Logistic map bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Table (6) summarizes the values of LEs for presented chaotic maps From the above table, it is observed that the dual tent has the most randomness whereas the single logistic map has the least randomness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table (6) summarizes the values of LEs for presented chaotic maps From the above table, it is observed that the dual tent has the most randomness whereas the single logistic map has the least randomness.…”
Section: Resultsmentioning
confidence: 99%
“…A compound of two 1-D chaotic maps suggests by I. Aouissaoui et al [6] for information security. Which achieved a logistic-sine map based on a tent chaotic map as well as a cubic-tent map but for SISO channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By integrating features of the sine map, logistic map, and tent map author in [21] suggested a novel compound one-dimensional piece wise chaotic system which is hybrid in nature to overcome the issues inherent in theses maps. The proposed map provides more chaotic characteristics than either map alone.…”
Section: Altered Sine-logistic Based Tent Map (Aslt)mentioning
confidence: 99%
“…Bifurcation diagram displays how the behavior of a chaotic system changes with a dynamic control parameter. And, the chaotic maps initial parameter, located in the chaotic areas, is selected using the Lyapunov exponent [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The Lyapunov exponent signs, λ, provide a qualitative picture of a system's dynamics.…”
Section: Chaotic Mapsmentioning
confidence: 99%